Fundamentals of Entrepreneurship ETR300 : Sanny Zeal Enterprise / Siti Sumaiyiah Liman... [et al.] - Liman, Siti Sumaiyiah; Yusop, Yunizar; Kasmudin, Norfaizah; Ali, Nazurah; Yusof, Amalina Anis (2010)
The name of our company is Sanny Zeal Enterprise. Our business is in the form of an enterprise which consists of five members. Each partner contributes certain amount of capital as agreed in the partnership agreement. The main business activity is selling premium quality palm sugar in the food and beverages market. There are no sleeping partners and all are entitled to participate in the business management. We have reached an agreement to entitle that Amalina Anis bt Yusof will act as our General 'Manager, Norfaizah bt Kasmudin as the Administrative Manager, Yunizar bt Yusop as the Operational Manager, Nazurah bt Ali acts as the Financial Manager and Siti Sumaiyiah bt Liman as the Marketing Manager. The selection of the General Manager is based upon the consensus among the partners and is selected based on the experience, skills and ability. The management team will be headed by the General Manager and assisted by the other managers. The General Manager is responsible in planning, leading, controlling and organizing the business- The Administration Manager is responsible for all administrative jobs such as planning and arranging the remuneration schedule of salaries and wages. The Operation Manager is responsible for the operation and will be supervising and coordinating the operation of the business. The Financial Manager will handle all financial matters such as preparing the budget and financial statements for the expenses of each departments and controlling the money flow of the organization Lastly, the Marketing Manager will be responsible to create the marketing plan, identifying customers' needs and demands, identifying the competitors, the target market and the market size and forecasting the future market.